Peptide receptor radionuclide therapy for metastatic paragangliomas - Pinato,DJ; Black,JRM; Ramaswami,R; Tan,TM; Adjogatse,D; Sharma,R (Medical Oncology, 2016)
There is little evidence to direct the management of malignant paragangliomas (mPGL) beyond initial surgical treatment. Peptide receptor radionuclide therapy (PRRT), using somatostatin analogues, is effective in other neuroendocrine tumours, but data on its efficacy in treating mPGL are scarce. We report safety and efficacy outcomes from a case series of five patients with advanced mPGLs treated with 177Lu-DOTATATE PRRT. The mean age of our cohort was 34 years (range 16–47); 4 patients were male with bone disease being the most prevalent metastatic site. PRRT scheme varied between 1 and 4 cycles, with premature cessation due to suspected pneumonitis in one case and disease progression in another. Three patients with previously documented progressive disease achieved stabilization following treatment; one had partial response and one was treatment refractory. Median progression-free survival was 17 months (range 0–78 months). 177-Lu-DOTATATE is an effective therapy in mPGLs in this molecularly defined patient cohort, warranting further investigation in larger studies including hereditary and sporadic mPGL.